Ammatoa Traditional System: Ethnographic Study of the Values of Social Structure and Environmental Sustainability - Pahenra A Nongko; Tri Indah Rusli; Patta Hindi Asis; Muhammad Agung Maugi; Muhammad Esya Kurniawan (Yayasan Keluarga Guru Mandiri, 2026)
This ethnographic study investigates the Ammatoa Kajang customary system in South Sulawesi, Indonesia, focusing on its